Development of superhydrophobic cotton fabric using zinc oxide nanoflower/polydimethylsiloxane (PDMS) nanocomposite coatings - Vijaya Kumar, Sorna Gowri (Array, 2021)
Nanoflower is anticipated to become a very smart material due to its unique properties such as high surface to volume ratio. A hydrothermal method was used in this study to prepare the zinc oxide (ZnO) nanoflower and characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FT-IR). The average particle size of the ZnO nanoflower was calculated as 21nm according to the Debye-Scherrer formula. The SEM result gives the surface morphological information of the ZnO nanoflower, which confirms the formation of the ZnO nanoflower. The ZnO nanoflower was dispersed in PDMS and coated onto cotton fabric to get the superhydrophobic fabric. The hydrophobicity was determined by measuring the water contact angle by the Sessile drop method and it was observed that coated fabrics have the highest contact angle, 140⁰ at 0.5% ZnO nanoflower concentration. The present study offers a method of fabrication of superhydrophobic cotton textile using ZnO nanoflower/PDMS polymer nanocomposites.